Longitudinal study on the impact of public health event control measures on physical fitness among Chinese adolescents: a southern city perspective - Chao Zhou; Aowei Zhang (BMC Public Health)
Abstract Since the World Health Organization declared COVID-19 no longer a public health emergency in 2023, over a year has passed. However, there has been insufficient research into whether the physical health of adolescents has recovered post-Pandemic. The COVID-19 Pandemic profoundly impacted the lives and health of adolescents globally, with prolonged lockdowns and social isolation measures potentially causing adverse effects on their physical health. This study aims to systematically evaluate the long-term impact of the Pandemic on the physical health of adolescents in a city in southern China. By analyzing data from over 48,000 tests, changes in various physical performance metrics, including Body Mass Index (BMI), Lung Capacity, endurance, speed, flexibility, and strength, were examined before, during, and after the Pandemic. The findings indicate that during and after the Pandemic, adolescents experienced an increase in BMI, while Lung Capacity and endurance significantly declined. Specifically, the average BMI for both Males and FeMales peaked after the Pandemic. Male Lung Capacity continuously decreased during and after the Pandemic, while FeMales saw a slight increase during the Pandemic but a significant drop afterward. In terms of endurance, male 1000-meter running times increased during the Pandemic and slightly improved afterward; however, female 800-meter running times increased during and after the Pandemic. Speed performance in the 50-meter sprint was best pre-Pandemic, worst during the Pandemic, and showed recovery post-Pandemic. Strength indicators, such as standing long jump, pull-ups (Males), and sit-ups (FeMales), displayed varying degrees of change, reflecting a decline in physical strength during the Pandemic. Additionally, flexibility improved throughout the period, peaking post-Pandemic. The study reveals the complex and multifaceted effects of Pandemic control measures on adolescent physical health. These findings are crucial for informing future public health policies and interventions aimed at supporting adolescent health during crises. The novelty of this research lies in its comprehensive and quantitative analysis of the Pandemic’s impact on various physical health metrics, providing valuable insights for subsequent studies and policy formulation.